Tafsir Putusan Mahkamah Konstitusi Tentang Sengketa Kepemilikan Pulau Berhala - Muh. Risnain (Jurnal Konstitusi, 2014)
The Decicion  of Constitutional Court concerning Berhala Island not a dispute  of property belonging under civil law. This dispute are constitutionality of the law concerning establishsing a new local government to the UUD 1945. Under Decicion of Constitutional Court in case No. 32/PUU-X/2012 and No. 62/PUU-X/2012 judge of Constitutional Court interpretation law about establishsing a new local government not based on legal constitutionality of that law to the UUD 1945. The interpretation of judge of Constitutional Court based on recognition and respective to high court decicion in case judicial review about Berhala Island.